LEUKOCYTES DIFFERENTIATION OF Pangasius hypophthalmusFED WITH Rhizophora apiculata EXTRACT ENRICHED PELLETS - Elfira Stefani Priska; Henni Syawal; Morina Riauwaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The aim of this study was to obtain the best dose of Rhizophora apiculata leaf extract added to the feed to prevent Motile Aeromonas Septicemia (MAS) as seen from the differentiation of leukocytes of siam jambal fish (Pangasius hypophthalmus). The method used is the experimental method with Completely Randomized Design (CRD), one factor with 5 levels of treatment and three replications. Kn: Negative control (feeding without being given R. apiculata leaf extract and without being challenged with A. hydrophila bacteria), Kp: Positive control (feeding without being given R. apiculata leaf extract and tested challenged with A. hydrophila bacteria), P1: Feed containing R. apiculata leaf extract at a dose of 1.5 mg/kg of feed, P2: Dose of 1.6 mg/kg of feed, P3: Dose of 1.7 mg/kg of feed. Siam Jambal fish (P. hypophthalmus) in size 8-10 cm are kept in an aquarium measuring 40×30×30cm with a stocking densities of 10 tail/aquarium, feeding as much as 10% of the body weight of fish and feeding three times a day. Taking the blood of the tested fishes was done 3 times, namely at the beginning of maintenance, after 30 days of maintenance and 14 days after the test challenged with A. hydrophila. The results of research show that P3 (Feed containing R. apiculata leaf extract with a dose of 1.7mg/kg of feed) was the best treatment with a total value of Leukocytes 11.72×104 cells/mm3, Lymphocytes 83.33%, Monocytes 8.67%, Neutrophils 8.00%, Phagocytic Activity 36.33%, and Survival Rate 80%. It can be concluded that feeding containing R. apiculata leaf extract can prevent Motile Aeromonas Septicemia (MAS) disease A. hydrophila and can increase the non-specific immune response of siam jambal fish. Keywords:Leukocyte,Pangasius hypopthalmus,Rhizophora apiculata, Aeromonas hydrophila